2020
DOI: 10.1159/000505976
|View full text |Cite
|
Sign up to set email alerts
|

Osthole: A Traditional Chinese Medicine for Ocular Anti-Angiogenic Therapy

Abstract: Osthole is an agent isolated from Cnidium monnieri (L.) Cusson and has been used to treat several disorders. Corneal neovascularization is a sight-threatening condition associated with several inflammatory or infectious ocular disorders. In this study, we investigated the anti-angiogenic effects of osthole on corneal neovascularization and the underlying mechanism. Methods: MTT assay, HE staining, and calcein-AM/propidium iodide staining was conducted to detect the toxicity of osthole in vitro and in vivo. Cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…e treatment is based on tonifying the liver and kidney, accompanied by removing the blood stasis and clearing collaterals, thus reducing the production of pathological VEGF [25][26][27][28][29]. Contemporary pharmacological studies show that part of traditional Chinese medicine for supplementing the liver and kidneys has antioxidation, stabilizes the blood-eye barrier, and has sex hormone-like effects [30][31][32][33][34]. In the clinical treatment of eye disease with the liver and kidney Yin syndrome, the use of Western medicine can be reduced to a certain extent by considering the combination of traditional Chinese and Western medicine.…”
Section: Discussionmentioning
confidence: 99%
“…e treatment is based on tonifying the liver and kidney, accompanied by removing the blood stasis and clearing collaterals, thus reducing the production of pathological VEGF [25][26][27][28][29]. Contemporary pharmacological studies show that part of traditional Chinese medicine for supplementing the liver and kidneys has antioxidation, stabilizes the blood-eye barrier, and has sex hormone-like effects [30][31][32][33][34]. In the clinical treatment of eye disease with the liver and kidney Yin syndrome, the use of Western medicine can be reduced to a certain extent by considering the combination of traditional Chinese and Western medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Osthole (OST) (7-methoxy-8-(3-methyl-2-butenyl)-2H-1-benzopyran-2-one) is a natural coumarin and a major chemical constituent of the plant Cnidium monnieri (L) Cusson and is considered a promising natural product that could be used pharmacologically in the future. These include anti-cancer [24][25][26] anti-inflammatory, [27][28][29][30] antioxidant, 31 anti-angiogenic, 32 anti-allergic 27,33,34 immunomodulatory 33,35 and hepatoprotective [36][37][38] activities. In our previous publications, we found that OST is immunosuppressive in peripheral blood mononuclear cells (PBMCs) isolated from children with allergies or asthma 27,30,[39][40][41][42][43] and autism spectrum disorders (ASD), in keratinocytes and fibroblast cell lines 28, and in a 3D skin model.…”
Section: Introductionmentioning
confidence: 99%
“…Osthole (OST), also known as methoxyparsleyol, was the first coumarin derivative obtained from medicinal plant Cnidium monnieri (L.) Cusson ( Figure 1 ) [ 12 , 13 ]. OST has anti-cancer effects against many types of cancer such as breast cancer, hepatocellular carcinoma, and kidney cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%